1, 3, 4‐Thiadiazolidine‐2, 5‐dione: Crystal Structure, Calculation of Aromaticity and Photodecomposition Quantum Yield. (21st May 2014) - Morsing, Thorbjørn J.; Schau‐Magnussen, Magnus; Døssing, Anders
<x xml:space="preserve">Abstract</x> Single crystals of 1, 3, 4‐thiadiazolidine‐2, 5‐dione (1) have been grown and the X‐ray crystal structure showed the molecule to be planar with sp2‐hybridized nitrogen atoms. Density functional theory calculations of nucleus‐independent chemical shifts profiles show that 1 is non‐aromatic. From actinometry, it was found that continuous photolysis of 1 in methanol at λ = 254 nm resulted in a decomposition with the quantum yield Φ = 0.076(7) mol/Einstein at room temperature.